PKM Penguatan Kapasitas Sdm Desa Pelatihan Manajemen Dan Keterampilan Teknis Untuk Pembangunan Lokal - Edi Wahyudin; Martanto; Fatihanursari Dikananda; Rano; Nasakh (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program (PKM) titled "Strengthening Village Human Resources: Management and Technical Skills Training for Local Development" aims to address the limitations in human resource capacity that often hinder development in villages. This program is designed to enhance the managerial skills of village officials and develop the technical skills of residents in agriculture, crafts, and information technology. Implementation begins with needs identification through surveys and interviews, followed by the design of an appropriate curriculum, and the delivery of training by experts and practitioners. The results of this program show a significant improvement in the managerial abilities of village officials and the technical skills of residents, contributing to the development of local businesses and the village economy. Evaluations also indicate an increased awareness of the importance of strengthening human resource capacity for sustainable development, making this program a potential model for other villages.